Palmitate induces Ros generation and actives inflammation pathway - Colia, Anna Laura; D’Apolito, Maria; Pettoello-Mantovani, Massimo; Brownlee, Michael; Giardino, Ida; Maffione, Angela Bruna (Italian Journal of Anatomy and Embryology, 2018)
Obesity is a social and economical problem. The prevalence of obesity has risen to epidemic proportions and continues to be one of the major worldwide health problem. Concurrent with the global obesity epidemic, there is an increasing number of people of all ages developing chronic kidney disease associated with obesity(1). Although obesity is often associated with dia- betes and hypertension, which are two of the most common risk factors for the development of end-stage renal disease (ESRD), obesity in itself can be an independent risk factor for both chronic kidney disease (CKD) and ESRD. The signaling pathways leading to renal pathology in obesity are not well understood. Here we investigate the hypothesis that physio-pathological concentration of palmitate induces reactive oxygen species production in conditioned human podocytes cell line through the activation of mitochondrial mechanisms , induces endoplas- mic reticulum (ER) stress and increases HMGB1 expression and inflammation. The condition- ally immortalized human podocytes cell line were differentiated and then treated with/without palmitate conjugated with BSA in a control and physio-pathological condition(2) and cell mor- phology, under sperimental conditions, were evaluated. Physio-pathological palmitate concen- trations stimulate ROS generation in human podocyte and induces endoplasmic reticulum (ER) stress in podocytes. Moreover palmitate- induced ROS caused the activation of pro-inflammato- ry pathways (p65/NfkB and MCP-1), up-regulation of TGF-β well identified as a central media- tor in renal fibrosis and induces a significantly increase of gene expression of HMGB1. Nor- malization of mitochondrial ROS production prevented each of these effects of palmitate. These results showed that palmitate at physio-pathological concentrations is able to induce ROS pro- duction, ER stress, inflammation, fibrosis and dysregulation of HMGB1 in human podocytes.